2004
DOI: 10.1159/000076419
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Power and Coherence Analyses Suggest Altered Brain Function in Abstinent Male Heroin-Dependent Patients

Abstract: Previous studies have shown that drug abuse is associated with altered brain function. However, studies of heroin abuse-related brain dysfunctions are scarce. Electroencephalographic (EEG) power and coherence analyses are two important tools for examining the effects of drugs on brain function. In the present study, we compared EEG power and coherence measures of 18 abstinent heroin-dependent subjects with those of 12 healthy control subjects. Furthermore, within the heroin group, associations between heroin u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
62
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 46 publications
(57 reference statements)
8
62
0
Order By: Relevance
“…It measures the functional interaction between cortical areas in different frequency bands. A high level of coherence between two EEG signals indicates a coactivation of neuronal populations and provides information on functional coupling between these areas (Franken, Stam, Hendriks, & van den Brink, 2004). De Bruin et al (2004) and De Bruin, Stam, Bijl, Verbaten, and Kenemans (2006 investigated the pure effects of alcohol intake on synchronization of brain activity while minimizing the confounding influence of genetic factors related to alcohol dependence.…”
Section: Qeeg In Sudmentioning
confidence: 99%
See 3 more Smart Citations
“…It measures the functional interaction between cortical areas in different frequency bands. A high level of coherence between two EEG signals indicates a coactivation of neuronal populations and provides information on functional coupling between these areas (Franken, Stam, Hendriks, & van den Brink, 2004). De Bruin et al (2004) and De Bruin, Stam, Bijl, Verbaten, and Kenemans (2006 investigated the pure effects of alcohol intake on synchronization of brain activity while minimizing the confounding influence of genetic factors related to alcohol dependence.…”
Section: Qeeg In Sudmentioning
confidence: 99%
“…Qualitative changes were observed in more than 70% of heroin addicts in the early abstinence (acute withdrawal) period; these included low-voltage background activity with diminution of alpha rhythm, an increase in beta activity, and a large amount of low-amplitude delta and theta waves in central regions (Olivennes, Charles-Nicolas, & Olievenstein, 1983;Polunina & Davydov, 2004). Franken et al (2004) found that abstinent heroindependent participants have an enhanced fast beta power compared with healthy controls, and this finding is concordant with other EEG studies on alcohol and cocaine abusing participants (Costa & Bauer, 1997;Herning, Glover, Koeppl, Phillips, & London, 1994;Rangaswamy et al, 2004;Roemer, Cornwell, Dewart, Jackson, & Ercegovac, 1995). Spectral power and ERPs in heroin addicts strongly relate to abstinence length (Bauer, 2001b;Polunina & Davydov, 2004;Shufman et al, 1996).…”
Section: Qeeg In Sudmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that Electroencephalogram (EEG) power may be more related to pre-morbid individual differences rather than to the effects of drug abuse. 12 …”
mentioning
confidence: 99%